Feasibility of Producing Activated Carbon from Tamarisk Biomass for the Removal of Water Pollutants via Adsorption (Al-Farooq Journal of Sciences, 2026)
This study aims to evaluate the potential of locally producing activated carbon from Tamarix spp. and assessing its efficacy as a sustainable adsorbent for wastewater remediation. The activated carbon was synthesized via carbonization followed by chemical activation. The adsorptive performance was primarily evaluated using methylene blue (MB) dye, achieving a significant removal efficiency of approximately 95% from aqueous solutions. Furthermore, the study investigated the removal of hydrocarbon pollutants, specifically benzene and propanol. The results indicated that the adsorbent in powdered form exhibited superior performance compared to its granular counterpart, with removal rates reaching approximately 37% for benzene and 18% for propanol. Characterization of the produced activated carbon revealed a high specific surface area and a robust capacity for pollutant sequestration. These findings suggest that Tamarix-derived activated carbon serves as a cost-effective and environmentally sustainable alternative for advanced water treatment applications.